A clinical, cytogenetic, and molecular study of 40 adults with the Prader-Willi syndrome. Issue 3 (March 1995) - Webb, T; Clarke, D; Hardy, C A; Kilpatrick, M W; Corbett, J; Dahlitz, M
Abstract : A clinical, cytogenetic, and molecular study has been carried out on 40 adults with a firm diagnosis of Prader-Willi syndrome. A cytogenetically detectable deletion was observed in 58% while further subjects had a deletion which was detectable by molecular methods only, giving a total of 76%. Four cases of maternal uniparental disomy (UPD) were all female. Three of them were heterodisomic while the fourth was isodisomic. Two male probands were heterozygous at all loci tested yet did not have UPD. Although methylation studies showed that one of them had a single band using probe PW71, the other one had two bands. Psychiatric studies suggest that females with maternal UPD are indistinguishable psychologically from those with a paternal deletion in 15q11q13.